Spillover Use and Innovation Success: What Role Does R&D Play? - Uwe Jirjahn (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2012)
Based on data from Germany, this study finds a positive link between using knowledge spillovers from rivals and innovation success in establishments without R&D but not in establishments with R&D. This supports the hypothesis that rivals knowledge is more valuable to establishments that are below the frontier of technology and product development.
Keywords: L60; O31; O32; 330; Corporate Spillover asymmetry; R&D; Learning; Product innovation